Energy Transition and Economic Growth in Asia Region: Evidence with Panel Quantile Regression - Sabir, Sabir; Rahman Razak, Abd.; Fernandes, Adji Achmad Rinaldo; Idris, Aditya (International Journal of Energy Economics and Policy, 2025)
Countries in the Asia region are increasingly aware of the importance of realising the Sustainable Development Goals (SDGs), The energy transition policy that has been carried out will affect their economic growth, so this research is focused on an in-depth study of the effect of energy transition on the economic growth of countries in Asia region. The results show that this study reveals that the energy transition plays an important role in driving economic growth in the Asia region. Variables such as sustainability and regulation as well as political commitment are shown to have a significant influence on increasing economic growth, highlighting the importance of policies that support clean energy. However, other results also suggest a potential trade-off between sustainability and economic growth for Asia countries in the short term, emphasising the need for a cautious approach in designing energy transition policies in the region.